2023
DOI: 10.3934/qfe.2023009
|View full text |Cite
|
Sign up to set email alerts
|

Does industrialization trigger carbon emissions through energy consumption? Evidence from OPEC countries and high industrialised countries

Abstract: <abstract> <p>This study investigated the effect of Industrialization on carbon emissions through energy consumption for a panel of eight Organization of the Petroleum Exporting Countries (OPEC) and nine High Industrialised Countries over the period 1985 to 2020; the study employs the first generation and second-generation Unit root tests. The study further adopts the use of the Panel Autoregressive Distributed Lag Model, and Common Correlated Effect pooled mean group to estimate the parameters of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…As China is in the nascent stage of sustainable financial investment, a more significant financial gap must exist for firms to shift from production based to environment based (Liu et al, 2023). At the same time, the study confirms that energy industrialization has a significant positive impact on carbon emissions in the short term, reducing environmental performance undertakings (Idowu et al, 2023). This is despite heavily polluting firms being more likely to commit to reducing environmental pollution, improving social responsibility, and obtaining more long-term and lasting benefits.…”
Section: Nature Of Environmental Pollution In the Industrymentioning
confidence: 54%
“…As China is in the nascent stage of sustainable financial investment, a more significant financial gap must exist for firms to shift from production based to environment based (Liu et al, 2023). At the same time, the study confirms that energy industrialization has a significant positive impact on carbon emissions in the short term, reducing environmental performance undertakings (Idowu et al, 2023). This is despite heavily polluting firms being more likely to commit to reducing environmental pollution, improving social responsibility, and obtaining more long-term and lasting benefits.…”
Section: Nature Of Environmental Pollution In the Industrymentioning
confidence: 54%
“…The study suggested that industrialisation increases carbon emissions in all developmental stages. From industrialised economies, the work of Idowu et al (2023) investigated whether energy consumption due to industrialisation leads to environmental degradation in OPEC and highly industrialised economies. The findings of their study found that industrialisation on emissions is negative for OPEC countries, and for highly industrialised countries, it is positive and significant.…”
Section: Literature Surveymentioning
confidence: 99%
“…Climate change is already one of the most important topics discussed globally by world leaders. Countries meet regularly to seek solutions and advocate for policy actions to mitigate its impacts [69]. This study explores the implications of organizational employees' cognitions of corporate ESG performance on green innovation outcomes and examines the moderating role of digital transformation in this dynamic.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%